Pelatihan Artificial Intelligence for Social Impact untuk Mahasiswa Program Kampus Merdeka - Utih Amartiwi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Artificial Intelligence (AI) is a branch of computer science that concerned with building smart machines capable of performing tasks that typically require human intelligence. Some people got misconception about AI that think AI would replace human but it is not. The main purpose of AI is to make our task become easier, faster, and efficiently. In this training, participants learned how to implement AI to solve the problem in our community. The participants are divided into 5 teams that develop an AI application to solve some issues in